Amamangun Karyanenak Tyasing Sasama: The Function of Slametan in Supporting Community Mental Health through the Perspective of Empowerment and Social Participation in Javanese Society - Bayu Adiputro; Carla Raymondalexas Marchira; Sumarni Djaka Waluya (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
The slametan tradition in Javanese culture plays an important role in supporting community mental health through strengthening social capital and social engagement. This review aims to explore more deeply the function of the slametan tradition in supporting community mental health through the dimensions of social empowerment and active participation. This paper is a literature study, which uses a critical review of sources obtained through various scientific portals. As a communal ritual, slametan strengthens social bonds, allowing emotional support that helps individuals cope with stress and psychological crises. In addition, the elements of offerings in slametan reflect the harmony between humans, nature, and the spiritual world, which strengthens the sense of solidarity among community members. Although modernization and urbanization present challenges to the sustainability of this tradition, the core values ​​of slametan, such as mutual cooperation and solidarity, can be adapted to the context of modern life. Slametan even has the potential to become a discussion platform on mental health in urban communities. Thus, slametan not only survives as a spiritual tradition but also functions as a collective coping mechanism that supports the psychological well-being of the community. This study highlights the importance of maintaining and adapting slametan to remain relevant in the face of dynamic social changes, so that this tradition can continue to contribute positively to community mental health.